Hubungan Psikopatologi dan Mekanisme Koping dengan Internet Gaming Disorder (IGD) pada Populasi Dewasa di Indonesia - Assandi, Pratiwi; Siste, Kristiana; Tobing, Heriani; Kusumaningrum, Profitasari (Jurnal Kedokteran Meditek, 2025)
Introduction: Psychopathology and maladaptive coping can contribute to Internet Gaming Disorder (IGD) in adults, threatening productivity and life. Purpose: This study aimed to explore the associations between psychopathology and coping mechanisms with IGD in Indonesian  adults. Methods: This cross-sectional study included 358 adults aged 18 to 59 who engaged in online gaming through consecutive sampling. Data were collected online using Symptoms Check List-90, Brief COPE, Ten-Item Internet Gaming Disorder Test, and sociodemographic questionnaire and were analyzed using chi-square, Kolmogorov Smirnov, Mann-Whitney, and logistic regression tests. Results: The IGD proportion was 16,5%. Psychopathology (somatization, obsessive-compulsive, interpersonal sensitivity, depression, anxiety, hostility, phobia, paranoia, and psychotic), coping mechanisms (active-coping, use of instrumental support, humor, use of emotional support, positive reframing, self-distraction, denial, substance use, behavioral disengagement, venting, and self-blame), age, marital status, gaming duration, and Multiplayer Online Battle Arena games were significantly associated with IGD (p<0,05). Gaming duration exceeding three hours per day (OR=3,220, CI=1,574-6,588), dysfunctional coping (OR=1,154, CI=1,067-1,248), and hostility (OR=7,231, CI=3,038-17,213) identified as risk factors, while venting (OR=0,727, CI=0,533-0,991) served as protective factor. Conclusion: Psychopathology and dysfunctional coping are associated with IGD. Education on related factors, early detection of psychopathology, and identification of coping mechanisms support comprehensive IGD management.